Curve fitting as a tool for comparing IDEB and IDEPE indicators in the municipality of Caetés, state of Pernambuco (Research, Society and Development, 2022)
Educational indicators help to monitor the functioning of educational networks and provide subsidies for the formulation of educational policies. The Basic Education Development Index (IDEB) is the national educational Brazilian indicator calculated biennially by the National Institute of Educational Studies and Research Anísio Teixeira (INEP), in contrast, the Pernambuco Education Development Index (IDEPE) is the educational indicator in Pernambuco calculated annually by the Pernambuco State Department of Education. Both are obtained by combining data on school flow and student performance in large-scale national and state assessments, respectively. This work aimed to carry out a study with the purpose of comparing the IDEB with the IDEPE in the final and initial years of the municipality of Caetés (PE). For this, we sought, through the curve fitting method, to identify a better model for the IDEB, adjusting the values ​​​​to the equations in order to obtain results of this indicator in the years 2013 to 2019 and to observe, through the generated curves, if these results could replace those of IDEPE released in the period in question. Discussions involve the contents of educational indicators, curve fitting and coefficient of determination. The adjustments test the hypothesis that the IDEB values, if inserted into the model, could make it possible to predict the IDEPE results and, consequently, the need for this last indicator. The hypothesis was refuted, since it was possible to conclude that the values ​​of the national indicator inserted in the model suffer a disparity in relation to the values ​​of the state indicator.